Superwarfarine Poisoning - Freixo, Ana (2015)
The superwarfarin-type anticoagulant rodenticides are used throughout the world and distinguish themselves from warfarin for its high potency and long acting anticoagulant activity. Easy access to these products enables the accidental or deliberate human poisoning. A case of voluntary rodenticide poisoning (RATIBRON®) by a woman who ingested an estimated 27.5 mg of bromadiolone total quantity for two weeks, with minor bleeding episodes, whose reversal of the anticoagulant effect with the correction of the abnormal values of the clotting tests took about one month to reverse is reported here. The correction of the haemostasis defects takes usually a long timeand there are no treatment guidelines, but a gradually vitamin K dosage reduction, as out patients, along with the monitoring of the International Normalized Ratio levels, allows a safe evaluation of the therapeutic response.